PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR AKTIVA DAN KEBIJAKAN DIVIDEN TERHADAP STRUKTUR MODAL PERUSAHAAN MANUFAKTUR DI BEI - Pertiwi, Ni Ketut Novianti Indah; Darmayanti, Ni Putu Ayu (E-Jurnal Manajemen, 2018)
The capital structure is important for the company because it involves the use of policy the most lucrative sources offunding, both from within and outside the company. The purpose of this research is to know the effect of profitability, liquidity, tangibility assets and dividend policy to capital structure. This research was conducted at manufactured companies listed on The Indonesia Stock Exchange periode 2016. Sampling was purposive sampling method and then obtained as many as 100 manufactured companies. The data used in this research is secondary data obtained from the financial statements contained in www.idx.co.id . The analysis technique used is multiple linear regression. Based on the analysis found that the liquidity and tangibility assets have significant effect to capital structure, profitability and dividend policy have unsignificant effect to capital structure.